Recommendations for behavior analysts regarding the implementation of Social Stories for individuals diagnosed with autism spectrum disorder. (18th August 2020) - Leaf, Justin B.; Cihon, Joseph H.; Ferguson, Julia L.; Milne, Christine M.; Leaf, Ronald; McEachin, John
Abstract : Social Stories have been implemented and evaluated clinically for individuals diagnosed with autism spectrum disorder. Social Stories are an intervention where an interventionist writes a story that describes a situation and the behaviors that the learner should display within that situation. Researchers have conducted literature reviews on Social Stories and in the majority of these reviews have found serious methodological flaws (e.g., Leaf et al., 2015; Styles, 2011; Reynhout & Carter, 2011). Yet behavior analysts continue to endorse, recommend, and implement Social Stories for individuals diagnosed with autism spectrum disorder. The purpose of this paper is to briefly review the literature on Social Stories, provide recommendations to behavior analysts on the use of Social Stories, and discuss how to best proceed when Social Stories are recommended in clinical settings.